"My Baby Went Straight to Heaven": Morality Work in Abortion Online Storytelling. (17th August 2021) - Combellick, Sarah Larissa
Abstract: Two competing activist narratives dominate public conversation around the morality of abortion, yet little empirical research examines how women talk about the morality of their own abortion experiences. Drawing on a qualitative analysis of 156 accounts from an abortion storytelling website, I find that traditional pro-choice moral arguments invoking privacy and bodily autonomy were apparent but not dominant in women's accounts. Three other frames emerged as ways to confront the problem of abortion as a morally controversial action: "abortion as morally unremarkable, " "abortion as morally problematic, but justified, " and "abortion as morally desirable." These frameworks varied in the degrees to which they aligned with politically acceptable abortion narratives. Throughout these frameworks were a number of overlapping themes, including motherhood, responsibility, and religion. Drawing on theories of morality work and moral accounts, I posit that subjects are able to hold a "tension of opposites" while still maintaining cohesive narratives and presenting positive moral identities. For example, many women assigned their fetus a moral status as a life or potential life, yet ultimately felt other factors outweighed the obligation to sustain that life. I argue that this tension is a significant feature of morality work that warrants more attention. Video Abstract: